2022
DOI: 10.3390/ijerph19020947
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Promotion and Intervention in Occupational Settings: Protocol for a Pilot Study of the MENTUPP Intervention

Abstract: Depression and anxiety are the most prevalent mental health difficulties in the EU, causing immense suffering and costing the global economy EUR 1 trillion each year in lost productivity. Employees in construction, health and information and communications technology have an elevated risk of mental health difficulties. Most mental health interventions for the workplace have been targeted at larger companies and small and medium-sized enterprises (SMEs) are often overlooked despite most people being employed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 91 publications
(112 reference statements)
0
34
0
Order By: Relevance
“…Results from experts representing the three sectors of construction, health, and ICT sectors, were consistent with responses from the experts with more general expertise. The results of the MENTUPP pilot trial [67] will show whether the intervention is similarly effective across sectors, but the consistency of expert responses suggests that our findings may be applicable in other workplace settings, although further research is needed.…”
Section: Discussionmentioning
confidence: 87%
“…Results from experts representing the three sectors of construction, health, and ICT sectors, were consistent with responses from the experts with more general expertise. The results of the MENTUPP pilot trial [67] will show whether the intervention is similarly effective across sectors, but the consistency of expert responses suggests that our findings may be applicable in other workplace settings, although further research is needed.…”
Section: Discussionmentioning
confidence: 87%
“…There is a lack of interventions with upstream primary-level approaches to improve the quality of psychosocial working conditions in an effort to prevent mental health problems and suicidal behavior that complement secondary and tertiary-level workplace interventions ( 33 , 36 ). Increased attention has especially been placed on multi-level workplace interventions that target changes in the entire organization (eg, workplace modifications to reduce stressors and enhance resources, mental health policies and cultural changes in relation to open discussion about mental health), among leaders/managers (eg, supervisor awareness training and skills training to handle mental health issues and to create healthy working conditions), in groups and teams (eg, peer support systems), and individual workers (increasing knowledge and resilience through education and training) with a range of promising projects underway, including large-scale EU Horizon 2020 funded projects such as MENTUPP and H-Work ( 38 , 39 ). While the COVID-19 pandemic has contributed to increased mental health challenges for some populations and workplace settings, in particular among people with pre-existing mental health conditions, proactive and innovative mental health interventions are required in the workplace, including digital intervention and prevention programs ( 38 , 40 ).…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Literature has shown that mental health promotion interventions in the workplace have been strongly associated with reduced absenteeism, presenteeism, and increased productivity [ 12 , 13 ]. However, there appears to be a lack of workplace-based interventions which promote mental health, particularly in the context of Small and Medium Enterprises (SMEs) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%